Wood and bark 137Cs contamination in black alder high-age stands in the near zone of the Chernobyl Nuclear Power Plant - Garbaruk, Dmitriy K.; Uglyanets, Anatoliy V. (Journal of the Belarusian State University. Ecology, 2022)
The results of the study of 137Cs contamination of wood and bark of black alder in high-age stands of the most common types of forest in the near zone of the Chernobyl Nuclear Power Plant are presented. The parameters of the accumulation of radionuclide by these tissues by types of forest and in general by formation are determined. The connection of their accumulation of 137Cs with the soil moisture index has been established. The features of the distribution of radionuclide in the wood of trees by classes of growth and development by Craft and by the radial profile of the trunk, as well as in the fallen deadwood, are revealed. Correlations of this radionuclide content in wood and bark with the density of soil contamination 137Cs and the distance to the place of its release have been established. Despite the high levels of contamination of the area, the Belarusian hygienic standard for harvesting round timber for the construction of walls of residential buildings and fuel wood corresponds to black alder wood in 7.7 % of ripe and overripe stands, for harvesting other round timber - in 26,9 %.